Integrated Chromatin Accessibility and Transcriptome Landscapes of Doxorubicin-Resistant Breast Cancer Cells - Wang, Xuelong; Yan, Jizhou; Shen, Baiyong; Wei, Gang (Frontiers in Cell and Developmental Biology, 2021)
Background: Doxorubicin is one of the most effective chemotherapeutic drugs for breast cancer while its common drug resistance leads to poor patient prognosis and survival. Growing evidence indicate dynamically reorganized chromatin allows rapid access of the gene regulatory machinery to open genomic regions facilitating subsequent gene expression through direct transcription factor (TF) activation and regulatory element binding. Methods: To better understand the regulatory network underlying doxorubicin resistance in breast cancer cells, we explored the systematic alterations of chromatin accessibility and gene expression by the assay for transposase-accessible chromatin using sequencing (ATAC-seq) in combination with RNA sequencing, followed by integrative analysis to identify potential regulators and their targets associated with differentially accessible regions (DARs) in doxorubicin-resistant MCF7 (MCF7-DR) cells. Results: A total of 3963 differentially expressed genes (DEGs) related to doxorubicin resistance were identified, including dramatically up-regulated MT1E, GSTP1, LDHB, significantly down-regulated TFF1, UBB, DSCAM-AS1, and histone-modifying enzyme coding genes HDAC2, EZH2, PRMT5, etc. By integrating with transcriptomic datasets, we identified 18,228 DARs in MCF7-DR cells compared to control, which were positively correlated with their nearest DEGs (r = 0.6). There were 11,686 increased chromatin-accessible regions, which were enriched in up-regulated genes related to diverse KEGG pathways, such as the cell cycle, regulation of actin cytoskeleton, signaling pathways of MAPK, PI3K/Akt and Hippo, which play essential roles in regulating cell apoptosis, proliferation, metabolism, and inflammatory responses. The 6,542 decreased chromatin-accessible regions were identified for the declined doxorubicin-associated biological processes, for instance, endocrine and insulin resistance, central carbon metabolism, signaling pathways of TGF-beta and P53. Combining data from TCGA, analyses of the DAR sequences associated with the DNA-binding motifs of significantly enriched TF families including AP-1, TEAD and FOX, indicated that the loss-function of FOXA1 might play a critical role in doxorubicin-resistant breast cancer cells (DOX-R BCCs). Conclusion: These data exhibit the non-genetic landscape of chromatin accessibility and transcript levels in the DOX-R BCCs, and provide clear insights and resources for the detection of critical TFs and potential cis-regulatory elements-based putative therapeutic targets.